The state relationship with religion: Defined through disciplinary procedures of accounting and regulation. (August 2019) - Cordery, Carolyn J
State regulation of charities is increasing. Nevertheless, although religious entities also pursue charitable objectives, jurisdictions often regulate them differently. In some states (including England until recently), the church (religious charities) are not called to account for their common-good contribution, despite owning significant assets and receiving public and government income. These regulatory and accounting variations emanate from a state's historically informed positional relationship with religion, which may be discordant against increasing religious pluralism and citizens' commonly-held beliefs. To open a debate on state–church relationships within the accounting history literature, this article analyses changes in England since 1534. It utilises a state–church framework from Monsma and Soper, combined with an application and extension of Foucauldian governmentality. The longitudinal study shows direct and indirect governmentality tools change with the state–church relationship. Such harmonisation of regulatory approach relies on citizens/entities subverting imposition of state demands which fail to meet their concept of common-good.